Effect of Nutrition Therapy on Ferritin in Pregnant Women with Anemia at Gamping 2 Public Health Center: Pengaruh Terapi Nutrisi Terhadap Ferritin pada Ibu Hamil Anemia di Puskesmas Gamping 2 - Shafriani, Nazula Rahma; Fauzia, Faurina Risca; Wahyuntari, Evi (Universitas Muhammadiyah Sidoarjo, 2022)
Anemia in pregnant women in Indonesia is 48.9% and has the potential to endanger the safety of the mother and child. The most common type of anemia is iron deficiency. The cause of iron deficiency is inadequate nutrient intake and increasing demand for Fe in pregnant women, causing a decrease in ferritin levels and hemoglobin levels below normal limits. The purpose of this study was to determine the effect of nutritional therapy for 2 months on hemoglobin and ferritin levels in anemic pregnant women. This research method is an experiment with a pretest-posttest control group design approach. This research was conducted on 2nd-trimester pregnant women who were diagnosed with anemia at the Gamping 2 Health Center with a total sample of 22 people. Respondents were taken by Simple Random Sampling, then divided into 2 groups, namely the case group 11 people who received nutritional counseling therapy and Fe supplements, and the control group 11 people who received Fe supplement therapy. Statistical analysis used the Independent t-test with the STATA 13 application. The results showed that there was no significant difference between Hb and ferritin levels in the control group and the case group with a p-value = 0.13 (p> 0.05) and p-value = 0.11 (p>0.05). So it can be concluded that there is no significant difference in Hb and Ferritin levels in pregnant women with anemia at the Gamping 2 Health Center between the case group and the control group.